An Integrated Stroke System Model Expands Availability of Endovascular Therapy While Maintaining Quality Outcomes - Lopez-Rivera, Victor (Stroke, 2021)
BACKGROUND AND PURPOSE: The optimal endovascular stroke therapy (EVT) care delivery structure is unknown, as the treatment is highly time-sensitive but also less efficacious in lower volume centers. Here, we present our experience in creating an integrated stroke system (ISS) to expand EVT availability throughout our region while maintaining hospital and physician quality standards. METHODS: We identified all consecutive patients with LVO AIS treated with EVT from Jan 2014 – Feb 2019 in our health care system. In Oct 2017 we implemented the ISS, in which 3 additional hospitals (4 total) became EVT performing hospitals (EPHs) and physicians were rotated between all centers. The cohort was divided by time into pre-ISS and post-ISS, and the primary outcome was time from stroke onset to EPH arrival. Secondary outcomes included hospital and procedural quality metrics. We performed an external validation using data from the SouthEast Texas Regional Advisory Council (SETRAC). RESULTS: Among 513 patients with LVO AIS treated with EVT, 58% were treated pre-ISS and 43% post-ISS. Over the study period, EVT procedural volume increased overall but remained relatively low at the three new EPHs (<70 EVT/year). After ISS, the proportion of patients that underwent inter-hospital transfer decreased (46% vs. 37%, p<0.05). In adjusted quantile regression, ISS implementation resulted in a reduction of time from stroke onset to EPH arrival by 40 minutes (p<0.01) and onset to groin puncture by 29 min (p<0.05). Rates of post-procedural hemorrhage, TICI 2b/3 and 90d mRS were comparable at the higher and lower volume EPHs. The improvement in onset to arrival time was not reflective of overall improvement in secular trends in regional pre-hospital care. CONCLUSIONS: In our system, increasing EVT availability decreased time from stroke onset to EPH arrival. The ISS provides a framework to maintain quality in lower volume hospitals.